Die Hikesie des Phemios und die Bedeutung von αὐτοδίδακτος in der Odyssee - Rösler, Wolfgang (Hyperboreus, 2015)
In book 22 of the Odyssey, Odysseus exacts revenge from the suitors and their supporters. The singer Phemius, who had been performing for the suitors in the palace, also fears for his life and therefore decides to turn to Odysseus as a suppliant. In a short speech (344–353), he tries to defend himself by arguing that the suitors forced him to perform his songs. In this context, he also mentions the origin of his singing: αὐτοδίδακτος δ’ εἰμί, θεὸς δέ μοι ἐν φρεσὶν οἴμας | παντοίας ἐνέφυσεν. This famous utterance is generally understood to refer to two distinct sources of his art: “Phemius is […] both self-taught and taught by a god” (Irene de Jong). In this article, a different understanding of αὐτοδίδακτος is suggested (following Pascale Hummel). According to this interpretation, Phemius, in fact, only refers to one source: “Spontaneously, I am endowed with inspiration. For (δέ) a god imbues (gnomic aorist) my mind with many ways of song”. This understanding perfectly suits the apologetic tone of Phemius’ speech: As Phemius makes clear, he is not himself responsible for his singing; rather a divine power causes him to sing.